Histochemistry of the surface mucous gel layer of the human colon. - Matsuo, K (1997)
BACKGROUND AND AIMS: Histochemical analysis of the surface mucous gel layer of the human colon is difficult, as it dissolves in fixatives. This study was undertaken to explore the surface mucous gel layer on the normal mucosa and neoplastic tissues of the large intestine. In addition, the distribution of different mucins secreted from goblet cells was studied with a series of histochemical stains for mucins. METHODS: Twenty four surgically resected specimens were fixed in Carnoy's solution and embedded in paraffin. In four cases, the surface mucous gel layer was also studied in frozen sections. Serial sections were stained by a battery of histochemical techniques characterising mucins. RESULTS AND CONCLUSION: The surface mucous gel layer consisted of the inner and outer layers. The first covered the luminal surface of the mucosa, consisted of mucins, and showed a vertical striped pattern. The second overlaid the first, showed a lateral striped pattern, and was contaminated with bacteria and other substances. Their thickness in paraffin sections varied considerably among the sites in the large intestine, but was the thickest in the rectum and measured 12.7 (SEM 6.0) microns and 88.8 (SEM 80.1) microns respectively. Mucins forming the inner layer were obviously derived from goblet cells underlying it.